Characterization of Volatile Organic Compounds and Aroma Sensory Properties in Yunnan Cigar - Yuping Wu; Haiyu Zhang; Wenyuan Wang; Guanghui Kong; Zaiming Li; Tikun Zhang; Miaochang Wang; Dong Yang; Chengming Zhang; Yongping Li; Jin Wang (Journal of Analytical Methods in Chemistry)
To characterize volatile organic compounds (VOCs) and aromatic sensory properties in Yun cigar, 27 samples from four origins were analyzed using SPME–HS–GC/MS and sensory analysis. The investigation results were analyzed using principal component analysis (PCA), Fisher linear discriminant analysis (LDA), and Pearson correlation analysis. In Yunnan cigars, the content of nicotine and neophytadiene accounted for over 90% of the total VOC content. Nicotine was significantly positively correlated with neophytadiene and phytol. The cigars from four origins were clearly classified by the PCA of VOCs. Four region discrimination functions were established through the LDA of 14 compounds, and the validation accuracy was 100%. The sensory descriptors with the highest geometric mean were woody, roasted, fresh-sweet, bean, and scorched. Acetophenone, megastigmatrienone A, and thunbergene were positively correlated with multiple aroma descriptors, while nicotine was negatively correlated with multiple aroma descriptors.